2019
DOI: 10.3390/socsci8100288
|View full text |Cite
|
Sign up to set email alerts
|

Attitude as a Mediator between Sustainable Behaviour and Sustainable Knowledge: An Approximation through a Case Study in the Dominican Republic

Abstract: The current ongoing globalisation shows an increasing amount of issues regarding sustainability, which is to be addressed from the very first stages. In this sense, different variables have been measured in the form of a survey in order to learn about the behaviour, attitude and knowledge of high school students in the Dominican Republic regarding sustainability, using a methodology based on structural equations through the SmartPls (v. 3.2.8) program. Among the main deductions, a mediation between their knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…It is therefore essential for the local authorities to focus on mechanisms to turn their willingness into actual recycling behaviour. Previous studies have produced similar results [22,36,37,54,55]. Therefore, the findings suggest that the more fashion design students' environmental knowledge is known, the more positive their attitudes towards sustainable fashion practices and thus the higher the likelihood that they will pay for behaviours towards sustainable fashion practices.…”
Section: Results Of Testing Research Hypothesessupporting
confidence: 71%
See 1 more Smart Citation
“…It is therefore essential for the local authorities to focus on mechanisms to turn their willingness into actual recycling behaviour. Previous studies have produced similar results [22,36,37,54,55]. Therefore, the findings suggest that the more fashion design students' environmental knowledge is known, the more positive their attitudes towards sustainable fashion practices and thus the higher the likelihood that they will pay for behaviours towards sustainable fashion practices.…”
Section: Results Of Testing Research Hypothesessupporting
confidence: 71%
“…Domínguez-Valerio et al [36] found that sustainability attitudes are a mediating variable between sustainability knowledge and sustainability behaviours, generating a full mediating effect. Casaló et al [37] argued that environmental knowledge fosters attitudes, and attitudes promote prosustainable behaviours.…”
Section: Attitudes and Behavioural Intentions For Sustainable Design ...mentioning
confidence: 99%
“…Data supported the mediating effect of EA between EQA, GSE and GPB but not between GT and GPB. Past studies also found support for the mediating effect of attitude in the link between subjective norm and intention to adopt Islamic banking (Bananuka et al , 2019) and between ethical aspect and counterfeit product purchase intention (Quoquab et al , 2017) and between sustainable knowledge and sustainable behaviour (Domínguez-Valerio et al , 2019).…”
Section: Discussionmentioning
confidence: 88%
“…Al-Naqbi and Alshannag [54] investigated 823 university students in the United Arab Emirates and found high levels of understanding, very strong positive attitudes, and moderate behaviour towards ESD and the environment. Dominguez-Valerio, Moral-Cuadra, Medina-Viruel, and Orgaz-Agüera [55] investigated the three interaction of these three variables with students in the Dominican Republic and found no influence of knowledge towards SD on behaviours towards SD, while attitudes functioned as a mediator between knowledge and behaviour. Withley, Takahashi, Zwickle, Besley, and Lertpratchya [56] found students with biospheric and altruistic values more likely to engage in environmental behaviours than students with egocentric values.…”
Section: Sustainability Knowledge Attitudes Perception and Behavioursmentioning
confidence: 99%